Management of the arrhythmic manifestations of cardiac sarcoidosis - Callum Cherrett; Callum Cherrett; William Lee; William Lee; William Lee; Nicole Bart; Nicole Bart; Nicole Bart; Rajesh Subbiah; Rajesh Subbiah; Rajesh Subbiah (Frontiers in Cardiovascular Medicine, 2023)
Cardiac sarcoidosis (CS) is characterised by a high burden of arrhythmic manifestations and cardiac electrophysiologists play an important role in both the diagnosis and management of this challenging condition. CS is characterised by the formation of noncaseating granulomas within the myocardium, which can subsequently lead to fibrosis. Clinical presentations of CS are varied and depend on the location and extent of granulomas. Patients may present with atrioventricular block, ventricular arrhythmias, sudden cardiac death or heart failure. CS is being increasing diagnosed through use of advanced cardiac imaging, however endomyocardial biopsy is often still required to confirm the diagnosis. Due to the low sensitivity of fluoroscopy-guided right ventricular biopsies, three-dimensional electro-anatomical mapping and electrogram-guided biopsies are being investigated as a means to improve diagnostic yield. Cardiac implantable electronic devices are often required in the management of CS, either for pacing or for primary or secondary prevention of ventricular arrhythmias. Catheter ablation for ventricular arrythmias may also be required, although this is often associated with high recurrence rates due to the challenging nature of the arrhythmogenic substrate. This review will explore the underlying mechanisms of the arrhythmic manifestations of CS, provide an overview of current clinical practice guidelines, and examine the important role that cardiac electrophysiologists play in managing patients with CS.